Pembuatan Brand Guidelines Untuk Perumahan The Oz Malang - Daniel Axel Geraldine (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This project carries a unique branding identity called Australian Living of Malang, which reflects the theme of Australian design and architecture, offering a comfortable and quality living experience. In an effort to strengthen its brand identity, PT Graha Bukit Utama realizes the importance of implementing consistent brand guidelines. Currently, the company faces challenges in terms of the use of logos and other branding elements that are inconsistent across various promotional platforms, both online and offline. This inconsistency has an impact on the trust of potential customers and reduces the impression of professionalism that should be presented by the brand. Therefore, the creation and implementation of brand guidelines is a crucial step that needs to be taken to overcome this problem. This project is planned to last for three months, starting from March 2024 to May 2024. During this period, this project is carried out in collaboration with the company to compile comprehensive brand guidelines. This design process will include several stages, starting from collecting relevant data, compiling the brand guidelines document itself, and socializing all stakeholders regarding the significance of having and implementing brand guidelines. Furthermore, an evaluation will be carried out to ensure that the company can implement the brand guidelines that have been designed properly. During the project implementation, it successfully carried out activities optimally and even exceeded the achievement of the KPI that had been set. This can be proven through the formation of brand guidelines that are compiled in print media format and soft files, which are ready to be used by the company in various marketing activities